Peran Strategis IAIN Ambon dan IAKN Ambon Dalam Merawat Toleransi Sosial dan Moderasi Beragama di Ambon Maluku - Mahyuddin Mahyuddin032 (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2020)
Tolerance and moderation in Indonesia are the discourses that have been much discussed lately. The government, community leaders including educational institutions are very active campaigning for these narrative. This study aims to describe the role of State Islamic Institute of Ambon (IAIN Ambon) and State Christian Institute of Ambon (IAKN Ambon) in preserving social tolerance and religious moderation. This article used qualitative research method. The authors collected data through interviews, observation, and documentation. The results of this study indicated that the consequences of past religious conflicts effect social tolerance and religious moderation in society. However, this threat can be dechipered by the two religius institutions by providing assistance and guidance to the wider community about the impotance of preserve harmony in diversity. In an effors to break down differences and antagonisms in society, Amobenese people were increangsingly being transformed into “harmony life” and out of the conditions of “suspicion and hostility” even though the relationship of religious groups still holds the strong potential for repeated social friction involving two religious groups.